PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION AGEN ASURANSI PT . PRUDENTIAL INDONESIA - Made Gede Arya Mandala Putra; Made Surya Putra (Faculty of Economics and Business Udayana University, 2014)
Insurance agent is an essential element in order to maintain the existence of the insurance companies in thebusiness competition. This study aimed to investigate the eff ect of j ob satisfaction and organizational commitmenton insur ance agent tur nover intention. This study was conducted at PT. PRUDENTIAL INDONESIA - Bali.Simple r andom sampling was used because of homogeneous population characterist ic. 160 questionnai reswere distributed, and only 155 questionnaires were returned by the respondents. Structural Equation Modeling(SEM) using AMOS 16.0 was used to test the research hypothesis. The resul ts of the study support all thehypothesis and indicate that job satisfaction has significant posi tive effect on organizational commi tment so itis advisable for the company to continue improvement of the job satisfaction of insurance agent s in order toenhance organizational commitment. In contrast, job satisfaction and organizational commitment consistentlyshow a negat ive and significant effect on turnover intention